Heterogeneous Photo-Fenton Decolorization Of Acid Green 25 Using Local Natural Clays And Dolomite Based Catalysts - Mohammad Azmi, Nur Hidayah (2012)
In this research work, three different type of catalysts from natural mineral resources were developed as heterogeneous catalyst support for the decolorization of Acid Green 25 (AG25) dye using photo-Fenton process in a batch system. Fe-Ipoh clay (Fe-IC), Fe-Bandar Baru clay (Fe-BBC) and Fe-Dolomite (Fe-DOL) were successfully synthesized by immobilized iron ions derived from ferric nitrate nonahydrate (Fe(N03)3.9H20) on the catalyst support, Ipoh clay (IC), Bandar Baru clay (BBC) and Dolomite (DOL), respectively through impregnation process. Preliminary studies on effect of calcination temperature ancl duration of time by all catalysts on decolorization of AG25 were investigated.